2003
DOI: 10.1109/tps.2003.820679
|View full text |Cite
|
Sign up to set email alerts
|

Optical observation of localized plasma after pulsed discharges in liquid helium

Abstract: A transient hot localized high-density plasma in liquid helium (LHe) after a pulsed discharge with a high voltage (20 kV, 180-360 A, 0.4-7 s) between tungsten (W) needle electrodes has been studied. Spatial and temporal changes of the plasma density in helium gas surrounded by LHe are measured by observing Stark broadening of 587.6-nm HeI spectral line. The localized plasma is found to have density above 10 16 cm 3 with an elongated ellipsoid in shape along the common axis of the needle electrodes. At 0.4 s af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…The microparticles in size of submicrometers to submillimeters have been called as dust grains or dust particles in the study of interstellar space as early as 1940s. Complex plasma has attracted much attention to the community of plasma physics [1][2][3][4], while recent advances in ultracold plasma [5][6][7][8][9] and cryogenic dusty plasma [10][11][12][13][14][15][16][17] challenge the basic understanding of plasmas. The Debye length, characterized by temperatures of electrons and ions, in a cryogenic plasma becomes much smaller than that in a conventional laboratory plasma and becomes comparable to the size of a dust particle.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microparticles in size of submicrometers to submillimeters have been called as dust grains or dust particles in the study of interstellar space as early as 1940s. Complex plasma has attracted much attention to the community of plasma physics [1][2][3][4], while recent advances in ultracold plasma [5][6][7][8][9] and cryogenic dusty plasma [10][11][12][13][14][15][16][17] challenge the basic understanding of plasmas. The Debye length, characterized by temperatures of electrons and ions, in a cryogenic plasma becomes much smaller than that in a conventional laboratory plasma and becomes comparable to the size of a dust particle.…”
Section: Introductionmentioning
confidence: 99%
“…A hot-filament discharge plasma was created in a vacuum chamber with an inner wall cooled by liquid nitrogen [20]. We produced cryogenic plasma by applying high voltage between needles in a gas cooled by liquid helium [7,9] where the plasma disappeared in a few seconds in a gas with 4 K electron temperature, or by applying high voltage between needles in liquid helium [8], where plasma disappeared in microseconds. Recently, we have succeeded to produce a steady plasma by an rf discharge in a vapor of liquid helium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments to inject ions by a high-voltage pulsed discharge (typically, 20 kV, 50 A, 1 lasec) in liquid helium stored in a Dewar bottle ( Fig. Density was determined by the Stark broadening [5]. Large gas bubbles were generated between tungsten needle electrodes in the discharge region and a highdensity plasma was produced.…”
Section: Plasma Production By a Pulsed Dischrge In Liquid Heliummentioning
confidence: 99%
“…A cryogenic complex plasma is an emerging field to study dust-plasma interaction in such an extreme condition as cryogenic temperature [3]. The early experiments suggested the possible production of cryogenic plasma in liquid helium environments [4,5], while an ultracold plasma was produced by the method of laser coohng [6,7]. The theoretical study of a complex plasma in the cryogenic environment suggested a unique nature of two-dimensional dust structure on the surface of liquid helium [8], while the cryogenic experimental studies revealed the low charge state of dust particles [9] and the superdense state of dust structure [10, 11,12].…”
Section: Introductionmentioning
confidence: 99%